Prototyping methods and constraints for small-to-medium sized enterprises in East Africa. (2018) - Chou, Suzanne; Austin-Breneman, Jesse
Abstract: Prototyping is integral to the design process for all projects, but particularly for small and medium-sized enterprises (SMEs). In resource-constrained contexts, designers must operate under unique constraints and opportunities. This study investigates the methods, constraints, and impacts on design outcomes of prototyping in seven design and manufacturing SMEs in East Africa. Results from a site visit to a Rwandan partner company as well as interviews with the engineering teams of the other organizations are presented. Practitioners reported that the main intent of prototyping in this context is to develop functional prototypes with increasing fidelity through a highly iterative process. This process was limited by constraints to manufacturing inputs, capabilities, and modeling predictions. These constraints contributed to increases in the time and cost for each iteration. Thus, results indicate that there may be a mismatch between the highly iterative method chosen and the constraints of the operating context.